Novel gold(III)-dithiocarbamate complex targeting bacterial thioredoxin reductase: antimicrobial activity, synergy, toxicity, and mechanistic insights - Ratia, Carlos; Ballén, Victoria; Gabasa, Yaiza; Soengas, Raquel G.; Velasco-de Andrés, María; Iglesias, María José; Cheng, Qing; Lozano, Francisco; Arnér, Elias S. J.; López-Ortiz, Fernando; Soto, Sara M. (Frontiers in Microbiology, 2023)
Antimicrobial resistance is a pressing global concern that has led to the search for new antibacterial agents with novel targets or non-traditional approaches. Recently, organogold compounds have emerged as a promising class of antibacterial agents. In this study, we present and characterize a (C^S)-cyclometallated Au(III) dithiocarbamate complex as a potential drug candidate. The Au(III) complex was found to be stable in the presence of effective biological reductants, and showed potent antibacterial and antibiofilm activity against a wide range of multidrug-resistant strains, particularly Gram-positive strains, and Gram-negative strains when used in combination with a permeabilizing antibiotic. No resistant mutants were detected after exposing bacterial cultures to strong selective pressure, indicating that the complex may have a low propensity for resistance development. Mechanistic studies indicate that the Au(III) complex exerts its antibacterial activity through a multimodal mechanism of action. Ultrastructural membrane damage and rapid bacterial uptake suggest direct interactions with the bacterial membrane, while transcriptomic analysis identified altered pathways related to energy metabolism and membrane stability including enzymes of the TCA cycle and fatty acid biosynthesis. Enzymatic studies further revealed a strong reversible inhibition of the bacterial thioredoxin reductase. Importantly, the Au(III) complex demonstrated low cytotoxicity at therapeutic concentrations in mammalian cell lines, and showed no acute in vivo toxicity in mice at the doses tested, with no signs of organ toxicity. Overall, these findings highlight the potential of the Au(III)-dithiocarbamate scaffold as a basis for developing novel antimicrobial agents, given its potent antibacterial activity, synergy, redox stability, inability to produce resistant mutants, low toxicity to mammalian cells both in vitro and in vivo, and non-conventional mechanism of action.